2013
DOI: 10.1002/mrc.4023
|View full text |Cite
|
Sign up to set email alerts
|

Leptocarposide: a new triterpenoid glycoside from Ludwigia leptocarpa (Onagraceae)

Abstract: A new triterpenoid bidesmoside (leptocarposide) possessing an acyl group in their glycosidic moiety (1), together with the known luteolin-8-C-glucoside (2) and 1-O-β-D-glucopyranosyl-(2S,3R,8E)-2-[(2'R)-2-hydroxypalmitoylamino]-8-octadecen-1,3-diol (3) was isolated from the n-butanol-soluble fraction of whole plant of Ludwigia leptocarpa (Nutt) Hara (Onagraceae). Structure of compound 1 has been assigned on the basis of spectroscopic data ((1)H and (13)C NMR, (1)H-(1)H COSY, HSQC, HMBC, and ROESY), mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…A leaf infusion has laxative, vermifugal and antidysenteric properties. Previous studies of this genus have revealed the presence of flavonoids, cerebrosides and triterpenoids [3,4]. A study recently reported that alcoholic extracts of L. octovalvis, L. abyssinica, L. decurrens and L. Leptocarpa, potentially have antioxidant, antibacterial and antifungal activities [2,5].…”
Section: Diarrhea Continues To Be One Of the Most Common Causes Of Momentioning
confidence: 99%
“…A leaf infusion has laxative, vermifugal and antidysenteric properties. Previous studies of this genus have revealed the presence of flavonoids, cerebrosides and triterpenoids [3,4]. A study recently reported that alcoholic extracts of L. octovalvis, L. abyssinica, L. decurrens and L. Leptocarpa, potentially have antioxidant, antibacterial and antifungal activities [2,5].…”
Section: Diarrhea Continues To Be One Of the Most Common Causes Of Momentioning
confidence: 99%
“…Concerning the glycosylation, the bonds with sugars can be recognized by the glycosylation shift: the formation of the ether linkage causes a downfield shift of the carbon values, while the esterification brings an upfield shift of the carboxylic carbon [42,47,61]. NMR is useful also in this framework.…”
Section: Glycosylation Site and Sugar Chain Branchingmentioning
confidence: 99%
“…Concerning the sugar chains, once the exact sequence of 1 H and 13 C of each sugar has been defined, the interglycosidic linkages have to be determined and the chain structure can be achieved once again by NMR, based on glycosylation shift and on HMBC correlations usually observed among the anomeric proton and the carbon of the second sugar involved in the linkage [39,49,54,56,61].…”
Section: Glycosylation Site and Sugar Chain Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…A leaf infusion has laxative, vermifugal, and antidysenteric properties. Previous studies of this genus have revealed the presence of flavonoids (19,20), cerebrosides, and triterpenoids (20,21). A study recently reported that alcoholic extracts of the leaves of L. octovalvis, L. abyssinica, and L. decurrens potentially have antioxidant, antibacterial, and antifungal activities (22,23).…”
Section: Introductionmentioning
confidence: 99%